Pengaruh Profitabilitas dan Likuiditas terhadap Struktur Modal pada Perusahaan Sub Sektor Batu Bara di BEI - Purnami, Ni Putu Sri; Susila, Gede Putu Agus Jana (Universitas Pendidikan Ganesha, 2021)
This study aims to examine the simultaneous and partial effect of profitability and liquidity on capital structure. The research design used was a causal quantitative design. The subjects in this study are the Coal Sub-Sector which is Listed on the Indonesia Stock Exchange and the objects of research are profitability, liquidity and capital structure. The sampling technique used was purposive sampling with a sample size of 22 companies. Data were collected by recording documents, then analyzed by multiple linear regression analysis. The results showed that (1) profitability and liquidity simultaneously or simultaneously had a significant effect on capital structure with a contribution of influence of 54.4%, (2) profitability had a positive and significant effect on capital structure with a contribution of influence of 32.4%, (3) liquidity has a negative and significant effect on the capital structure with an impact contribution of 36%.